ANALISIS HABITAT Alpinia eremochlamys K.Schum. DI HUTAN PEGUNUNGAN SEKITAR DANAU KALIMPA’A TAMAN NASIONAL LORE LINDU, SULAWESI TENGAH - Stevani Tamawiwi; Moh Iqbal; Ramadanil Pitopang (Biocelebes, 2020)
The research “vegetation analysis of Alpinia Eremochlamys K.Schum. Habitat in the mountain forest around Kalimpa’a lake, Lore Lindu National Park Central Sulawesi” has been conducted from August to November 2018. The objective of the research was investigate species in the habitat of Alpinia Eremochlamys K.Schum. and to measure enviromental condition. The research was used multiple plots method, where plots were observed sistematicaly. The results indicated that the vegetation at tree level dominated by Mallotus paniculatus Mull.Arg., a pole level was dominated by Elaeocarpussphaericus, vegetation of sapling by Vaccinium sp. and seeding level was dominated by Ageratum conyzoides L. The daily average temperature was 22.38°C, relative humidity was 70.16% and light intensity average of 387.3 lux.